PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MIA 1 SMA TRI BHAKTI PEKANBARU - ', Hardayati; ', Erviyenni; ', Miharty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research on the implementation of cooperative learning Numbered Head Together has been done to achieve student’s mastery learning on the subject of rate of reaction in class XI MIA 1 SMA Tri Bhakti Pekanbaru. Form of research is pra-experiment research with One-Shot Study Case design. data retrieval time from the date of 1 November to 17 November 2014. The sample was selected from a class of two classes, namely class XI MIA 1. Data analysis technique used is to calculate presentation of classical mastery learning. Based on the final results of data processing using acquired mastery learning classical is 85,71%, it’s means that the implementation of cooperative learning Numbered Head Together can achieve student’s mastery learning on the subject of rate of reaction in class XI MIA 1 SMA Tri Bhakti Pekanbaru. Keywords: Numbered Head Together, Mastery Learning, Rate of Reaction